Knowledge of prevention and treatment of infectious diarrhea among parents of children under five with diarrhea in Anhui province: an outpatient-clinic-based questionnaire survey - Yuanfang SUN; Yongkang XIAO; Lei GONG; Hongyuan WEI; Wanwan MA; Shuo FENG; Qiang ZHANG; Linlin LI; Qile WU; Jiabing WU (Zhongguo gonggong weisheng)
ObjectiveTo assess the status and determinants of knowledge of prevention and treatment of infectious diarrhea among parents of children aged ≤5 years with diarrhea to provide evidence for the development of targeted health intervention strategies. MethodsWe conducted face-to-face interviews with 1 325 parents of children aged ≤ 5 years diagnosed with infectious diarrhea at outpatient clinics of 8 grade II medical institutions selected by cluster sampling in 4 cities across geographic regions of Anhui province between May 2021 and October 2022. A self-developed questionnaire was used in the survey, which included the parental demographic information, general awareness of infectious diarrhea, and knowledge of infectious diarrhea prevention (10 questions with one point for each correct answer and a total score of 8 was defined as knowledge of the disease prevention) and treatment. A multivariate analysis of factors influencing parental knowledge of diarrhea prevention was performed using binary logistic regression, adjusting for potential confounders. ResultsOf the 1 155 participants with valid responses, 775 (67.1%) were considered knowledgeable about preventing and treating infectious diarrhea. The three questions with the lowest correct response rate were "Does using shared utensils or individual servings during group meals help prevent infectious diarrhea?" (correctly answered by 65.1% of participants), "Does eating food contaminated by flies, cockroaches, and other pests lead to infectious diarrhea?" (69.5%), and "Does frequent nail clipping help prevent infectious diarrhea?" (72.8%). Binary logistic regression analysis indicated that city of residence, monthly household income, education level, and occupation were significant factors influencing participants′ knowledge of infectious diarrhea. ConclusionAmong parents of children aged ≤5 years with diarrhea in Anhui province, general awareness of infectious diarrhea prevention is relatively low, especially among those with lower education levels and household income, suggesting that targeted health education on infectious diarrhea needs to be implemented in different populations.